2020
DOI: 10.1111/petr.13706
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma development in Fanconi anemia patients who underwent hematopoietic stem cell transplantation

Abstract: We examined SCC development of 24 FA patients, who received HSCT from HLA‐matched relatives. In our BMT center, we applied low‐dose CY + LFI + ATG (n:13) as conditioning regimen for FA patients between 1992 and 1999, and CY + BU + ATG (n:11) between 1999 and 2002. The aim of this study was to investigate SCC development after HSCT and examine features of the follow‐up patients. The 10‐year overall survival (OS) of the group with LFI + regimen was 43%, whereas the group without LFI regimen was 60%. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
1
Order By: Relevance
“…In relation to the indication for HSCT, among the selected studies, 12 patients out of 33 were affected by Fanconi Anemia (FA), a genetically and phenotypically heterogeneous autosomal recessive, dominant or X-linked disorder, characterized by congenital abnormalities, bone marrow failure, and increased risk for cancer [ 32 ]. HSCT is considered the treatment of choice in FA patients who develop hematopoietic failure, but it may predispose to late cancer development by adding risk factors; among these, a strong association between GVHD and late malignancies has been demonstrated [ 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the indication for HSCT, among the selected studies, 12 patients out of 33 were affected by Fanconi Anemia (FA), a genetically and phenotypically heterogeneous autosomal recessive, dominant or X-linked disorder, characterized by congenital abnormalities, bone marrow failure, and increased risk for cancer [ 32 ]. HSCT is considered the treatment of choice in FA patients who develop hematopoietic failure, but it may predispose to late cancer development by adding risk factors; among these, a strong association between GVHD and late malignancies has been demonstrated [ 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…conducted a study comparing diagnosis, treatment, and outcomes of OSCC in FA patients after HSCT, and found that the patients often ignore initial cancer symptoms. The delayed diagnosis contributed to the low survival rates 24 . Thus, despite a few studies reporting poor accuracy of oral self‐examination by FA patients and guardians, 23 educating the patients to perform proper self‐screening may be an effective auxiliary method combined with periodic professional evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed diagnosis contributed to the low survival rates. 24 Thus, despite a few studies reporting poor accuracy of oral self-examination by FA patients and guardians, 23 educating the patients to perform proper self-screening may be an effective auxiliary method combined with periodic professional evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reports of survivors of HSCT for FA demonstrated that 40%-70% (depending on the length of follow-up) of individuals developed squamous cell carcinoma of the head and neck region. 5,6 The situation with AT and adult-onset cancers is more complex as many patients with AT do not survive far into adulthood, given the combined risk of malignancy, immunodeficiency, and severe neurologic disability, resulting in tragic losses because of pulmonary failure during adolescence and young adulthood. 7,8 Dramatically different approaches for identifying every individual with a genetic condition in a geographic region have more recently involved genome-scale sequencing such as the study of individuals with DICER1 pathogenic variants in the Geisinger Health population 9 or conversely using highly specific and sensitive clinical features, for example, the astounding study where investigators systematically performed physical examinations on 152,819 six-year-old children in six German states using the neurofibromatosis type 1 diagnostic criteria to identify all individuals with neurofibromatosis type 1.…”
mentioning
confidence: 99%
“…Two recent reports of survivors of HSCT for FA demonstrated that 40%-70% (depending on the length of follow-up) of individuals developed squamous cell carcinoma of the head and neck region. 5 , 6 The situation with AT and adult-onset cancers is more complex as many patients with AT do not survive far into adulthood, given the combined risk of malignancy, immunodeficiency, and severe neurologic disability, resulting in tragic losses because of pulmonary failure during adolescence and young adulthood. 7 , 8 …”
mentioning
confidence: 99%